Grammaticalization and the etymology of Old Irish ocus 'and' - Griffith, Aaron (Studia Celtica Posnaniensia, 2024)
This paper integrates a philological investigation of Old Irish coordination with cross-linguistic accounts of the phenomenon in order to offer an etymology Old Irish ocus ‘and’. It is suggested that Pre-Irish employed ocus in a comitative coordination strategy (i.e. ‘A with B’). This started out as a nominal and adjectival coordinator. Late in the prehistory of Irish, this coordinator grammaticalized as the all-purpose ocus ‘and’ (i.e. ‘A and B’) that is found in Old Irish texts.